Decreasing Effectiveness of Organic and Inorganic Material in Liquid Waste of Leather Tanning by Using Waterlettuce (Pistia statiotes L.) as Biofilter - Mustaniroh, Siti Asmaul; Wignyanto, Wignyanto; S., Bernardus Endi (Jurnal Teknologi Pertanian, 2009)
This objective of the research was to know the ability of waterlettuce to decrease organic and inorganic materials in liquid waste of leather tanning, to know detention time needed by waterlettuce in decreasing organic and inorganic material, and to know the effectiveness of waterlettuce as biofilter compared to Eichhornia crassipes.  The research used completely randomized design with ten treatments (based on 10 days planed-detention time), with three replication.  Purified liquid waste was analyzed including pH value, BOD, DO, TSS and chromium content.  The data was analyzed using Test F on 5% significant level and Turkey Test.  Effectiveness analysis was used to know the range of waterlettuce effectiveness compared to Eichhornia crassipes. The results showed that waterlettuce (Pistia statiotes L.) as biofilter in liquid waste of leather tanning decreased pH value 39.25 %, BOD 67.05%; DO 72.24%, TSS 60.31%, and chromium content 74.51%.  Detention time of waterlettuce in decreasing organic and inorganic material in liquid waste of leather tanning was ten days.  Effectiveness of Waterlettuce as biofilter in liquid waste of leather tanning to decrease organic and inorganic is 99.33% of pH; 100.65% of BOD; 119.70% of DO; 10.16% of TSS and 103.05% of chromium content.Keywords: effectiveness, waterlettuce, biofilter, detention time